The unification bonus (malus) in postwall Eastern Germany - Miriam Beblo; Irwin L. Collier; Thomas Knaus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper presents estimates of the unification bonus for East Germans over the period 1991 to 1998. The unification bonus is defined as the discounted value of the difference between a person?s actual income and his or her counterfactual real income stream forecast for a hypothetical continuation of economic life in a static GDR. The two main issues tackled in this study are the construction of valid deflators for a comparison of real incomes during the transition from a centralized to a market economy and the estimation of plausible counterfactual income streams. Our central result is that 19 percent of East Germans received a present value malus and so can be regarded as unification losers but that the aggregate bonus is ten times the size of the aggregate malus of the sample.
Keywords: D3; D1; P2; 330; Real income comparison; income distribution and mobility; economies in transition; Kaufkraft; Lebensstandard; Einkommensverteilung; Systemvergleich; Neue Bundesländer; DDR; Nationale Einheit; Lebensstandard; Deutschland